UJI DOSIS PUPUK NPK PADA BEBERAPA VARIETAS PADI UNGGUL BARUEFFECT OF NPK FERTILIZER DOSAGES ON SOME NEW VARIETIES OF RICE PLANT (Oryza saliva L.)) - D. DARYANTI; TYAS SUMARAH KURNIA DEWI (JURNAL ILMIAH AGRINECA, 2009)
The research was done in Kelurahan Kauman Kidul, Kecamatan Sidorejo, Kota salatiga, from February until June 2008, the type of soil is Latosol, the altitude is 525 metere above sea level. This research was arranged in Split-plot Design. Kinds of varieties as main plot concisted of 3 levelsPepe, Sintanur and IR 64, and dosages of NPK fertilizer as sub plot consisted 4 levels0 kg/ha, 200 kg/ha, 250 kg/ha and 300 kg/ha. In this research Urea.fertilizer was still used 200 kg/ha .The datas were analyzed using analysis variance and Least Significant Difference of 5% level. The research showed that kinds of varieties influenced .significant to high of plant, total amount of bough, amount of productive bough, dry shel of rice plant, dry shel of rice milled weight per sample, but not significant to weight of fresh straw and dry straw, dry shel of rice weight per plot, and weight of 1000 seeds. Dosages of NPR" fertilizer influenced significant to high of plant, total amount of bough, weight of fresh and (by straw, weight of dry shell per sample and per plot, weight of dry rice milled per sample and per plot and weight of 1000 seeds. Combined effect from two treatments was significant to weight of dry shell milled per sample and per plot, and not sifnificant to other parameters. The highest yield from this research is6,417 ton/ha from treatment IR 64 variety and 300 kg/ha dosage NPK fertilizer, but statistically not significant different from treatment with Sintanur or Pepe varieties and dosage fertilizer is 250 kg/ha. From economics analysis knows that using sintanur and Pepe varieties with dosage fertilizer 250 kg/ha is more profit than IR 64.